EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN PEDIATRI DI INSTALASI RAWAT INAP UPTD KHUSUS RUMAH SAKIT UMUM HAJI MEDAN TAHUN 2024 - Elanda, Yurike; Sigalingging, Nurcahaya; Maulana H, Armansyah; Azizah, Umi Hani (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
One of the health problems is infection. Bacteria are the most common cause. Antibiotic use is increasing because of more bacterial infections. This condition can cause the risk of antibiotic resistance. In children, antibiotic resistance can occur in conditions that impact mortality, morbidity, and high medical costs. This study aims to determine the evaluation of antibiotic use and a description of the evaluation of antibiotic use with the ATC/DDD method from medical records of hospitalized patients receiving antibiotic therapy. The research method used is observational research (non-experimental) with a quantitative approach, which includes analysis of patient characteristics and antibiotic use patterns. The results showed that the cephalosporin antibiotic group (80.4%) was used most often. The most common type of antibiotic used was ceftriaxone (38.8%). The most common type of treatment was intravenous (56.1%). In quantitative evaluation using the ATC/DDD method, the antibiotic with the highest DDD/100 patient days value was cefixime, with 124.46, and the antibiotic with the lowest DDD/100 patient days value was Ripampicin, with 0.04. The conclusion of this study is based on the analysis of antibiotic use using the ATC/DDD approach, regarding the Medan Haji General Hospital in 2024. Antibiotic use was evaluated using the ATC/DDD approach, resulting in a total DDD/100 inpatient days value of 202.11%. Cefixime had the highest DDD/100 inpatient days value, which was 120.15%, with a total antibiotic length of stay (LOS) of 325 days.